1998
DOI: 10.1063/1.368964
|View full text |Cite
|
Sign up to set email alerts
|

Observations of and model for insular grains and grain clusters formed during anomalous grain growth in N18 superalloy

Abstract: Articles you may be interested inCavity morphology in a Ni based superalloy under heavy ion irradiation with hot pre-injected helium. II Cavity morphology in a Ni based superalloy under heavy ion irradiation with cold pre-injected helium. I

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 5 publications
(2 reference statements)
0
14
0
3
Order By: Relevance
“…Previously, Park et al [18] and Messina et al [19] measured the grain boundary misorientation angles for many penetrating microstructures at the growth front of abnormally growing grains including island and peninsula grains. These results showed that the penetrating microstructures at the growth front of abnormally growing grains are characterized by low-angle or CSL boundaries, which are energetically favorable for triple-junction wetting.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Park et al [18] and Messina et al [19] measured the grain boundary misorientation angles for many penetrating microstructures at the growth front of abnormally growing grains including island and peninsula grains. These results showed that the penetrating microstructures at the growth front of abnormally growing grains are characterized by low-angle or CSL boundaries, which are energetically favorable for triple-junction wetting.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Most of the developments in the theory of normal grain growth have been summarized in a review paper by Atkinson. [14] Hillert [2] developed a statistical theory of grain growth and suggested the equation:…”
mentioning
confidence: 99%
“…Most island grains are black and could be considered to have relatively low-energy boundaries. Based on the EBSD measurements showing that the misorientation angles between abnormally-growing grain and island or peninsular grains have mainly low angle or special boundaries, Messina et al 13) and Ko et al 14,15) suggested that island and peninsular grains are formed by solid-state wetting. Since the formation of island and peninsular grains are commonly associated with abnormal grain growth, their formation mechanism might be closely related to the abnormal grain growth mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…7,[13][14][15][16] Figure 1 shows a typical microstructure of an abnormally grown Goss grain in Fe3%Si steel. Many island and peninsular grains are observed inside the Goss grain.…”
Section: Introductionmentioning
confidence: 99%